Systemic QX-314 Reduces Bone Cancer Pain through Selective Inhibition of Transient Receptor Potential Vanilloid Subfamily 1–expressing Primary Afferents in Mice. (July 2016) - Fuseya, Satoshi; Yamamoto, Katsumi; Minemura, Hitoshi; Yamaori, Satoshi; Kawamata, Tomoyuki; Kawamata, Mikito
Abstract : Background: The aim of this study was to determine whether systemic administration of QX-314 reduces bone cancer pain through selective inhibition of transient receptor potential vanilloid subfamily 1 (TRPV1)–expressing afferents. Methods: A mouse model of bone cancer pain was used. The authors examined the effects of bolus (0.01 to 3 mg/kg, n = 6 to 10) and continuous (5 mg kg −1 h −1, n = 5) administration of QX-314 on both bone cancer pain–related behaviors and phosphorylated cyclic adenosine monophosphate response element–binding protein expression in dorsal root ganglion neurons (n = 3 or 6) and the effects of ablation of TRPV1-expressing afferents on bone cancer pain–related behaviors (n = 10). Results: The numbers of flinches indicative of ongoing pain in QX-314–treated mice were smaller than those in vehicle-treated mice at 10 min (3 mg/kg, 4 ± 3; 1 mg/kg, 5 ± 3 vs . 12 ± 3; P < 0.001; n = 8 to 9), 24 h (3 ± 2 vs. 13 ± 3, P < 0.001), and 48 h (4 ± 1 vs. 12 ± 2, P < 0.001; n = 5 in each group) after QX-314 administration, but impaired limb use, weight-bearing including that examined by the CatWalk system, and rotarod performance indicative of movement-evoked pain were comparable. QX-314 selectively inhibited the increase in phosphorylated cyclic adenosine monophosphate response element–binding protein expression in TRPV1-positive, but not in TRPV1-negative, dorsal root ganglion neurons compared to that in the case of vehicle administration (32.2 ± 3.0% vs . 52.6 ± 5.9%, P < 0.001; n = 6 in each group). Ablation of TRPV1-expressing afferents mimicked the effects of QX-314. Conclusion: This study showed that systemic administration of QX-314 in mice inhibits some behavioral aspects of bone cancer pain through selective inhibition of TRPV1-expressing afferents without coadministration of TRPV1 agonists. Abstract : In mice with behavioral evidence of pain and dysfunction after injection of cancer cells in bone, systemic QX-314, but not lidocaine, produced a long-lasting reduction in spontaneous flinching behavior by inhibiting transient receptor potential vanilloid subfamily 1–expressing nerves, but did not reduce activity-dependent disruption of behaviors.Supplemental Digital Content is available in the text.